Detection of β- lactamases enzymes responsible for β-lactam resistance among gram negative bacteria by PCR - Aziz, Rawa Abdul Redha; Sura Alaa Saud; . Jinan Azeez Thabit (Al-Qadisiyah Journal of Pure Science, 2021)
Abstract: Objective(s): β- lactamases enzymes are well studied in literature since they lead to β-lactam resistance among many pathogens, hence global concern of human and animal health issues is rising. The aim of study is to detect these kinds of enzymes among some gram negative bacteria isolated locally. Material and methods: 30 isolate of each gram negatives Citrobacter spp., Serratia spp., and Enterobacter spp. were obtained from different clinical samples in Baghdad and Al-Najaf cities through March 2020 until January 2021. Isolates were identified biochemically and by Vitek2 system. β- Lactamases encoding genes like (blaSHV (231bp), blaIMP-1 (500), blaVIM (382), blaAmp (1150), blaCMY (1014), bla oxa23 (501), and bla oxa51 (353bp) were detected by PCR. Results: It was found that (80%, 75%, 30%, 50%, 38%, 55%, and 69%) of Citrobacter spp isolates had β- Lactamases encoding genes (blaSHV, blaIMP-1, blaVIM, blaAmp, blaCMY, bla oxa23, and bla oxa51), respectively. Serratia spp. showed having (blaSHV, blaIMP-1, blaVIM, blaAmp, blaCMY, bla oxa23, and bla oxa51) among (20%, 85%, 60%, 28%, 40%, 67%, and 58%), respectively. There were also (60%, 50%, 25%, 33%, 60%, 81%, and 73%) of Enterobacter spp. isolates harbored (blaSHV, blaIMP-1, blaVIM, blaAmp, blaCMY, bla oxa23, and bla oxa51), respectively. Conclusion: Our findings revealed that most of gram negative bacteria isolated locally had different β- Lactamases encoding genes, leading to increase health problems among patients infected with those pathogens.